Pengaruh Pemanfaatan Lahan Pekarangan Rumah Terhadap Kejadian Stunting - Revika Gina Luthfiya; Sutarto; Reni Zuraida (CV. Jasa Sukses Abadi, 2022)
Stunting is an irreversible growth disorder that can be influenced by many factors, one of which is influenced by inadequate nutritional intake. The prevalence of stunting in Indonesia is still quite high, so various efforts have been made by the government to tackle the stunting problem. One of the efforts made is to socialize the use of yard land as an effort to prevent and deal with stunting. This article is a literature review compiled to determine the effect of nutritional intake from the home garden on the prevalence of stunted and non-stunted toddlers. The literature sources used in this article use national and international scientific articles published in 2013-2022. Nutritional intake which is the main cause is macronutrient intake, namely carbohydrate, protein and fat intake. Intake of macronutrients provides a large energy contribution to the level of daily energy adequacy. Energy deficit that occurs in toddlers aged 1-5 years is the biggest cause of stunting. Toddlers with stunting will experience chronic growth failure, if not treated immediately it will have a long impact until puberty. Utilization of the yard will affect the amount and type of variation in nutritional intake in toddlers, the diversity of commodities from the home yard will increase the nutritional intake of toddlers so as to avoid chronic malnutrition and stunting. Keywords: Stunting, Use of yard land, Nutritional Intake